C3 Reduced cell size and enhanced cell proliferation are characteristics of sthdhq111/111 cells and should be considered as possible confounding factors. (13th September 2016) - Clemens, Laura E; Walter, Carolin; Singer, Elisabeth; Weber, Jonasz J; Krahl, Ann-Christin; Mau-Holzmann, Ulrike A; Rischert, Nadine; Nguyen, Huu P
Abstract : Background: The ST Hdh cell lines are immortalised striatal precursor cells from wild type and Hdh Q111 knock-in mice and are commonly used to study the molecular aspects of HD. Morphological differences between the wild type and mutant cell lines exist, but are rarely described or clearly considered in published reports. Aims: The aim was to characterise cell size and proliferation differences in the ST Hdh cells, to investigate the importance of these phenotypes for HD and their possible confounding nature. Methods: Cell size, cell proliferation, mTOR-related cell signalling and chromosome content were assessed in wild type ST Hdh Q7/7 and HD mutant ST Hdh Q111/111 cell lines as well as in primary cultures of mouse embryonic fibroblasts (MEF) established from the same mouse model (MEF Hdh Q7/7 and MEF Hdh Q111/111 cells). Cell viability and cell death were measured in ST Hdh cells using standard fluorometric assays and flow cytometry. Results: ST Hdh Q111/111 as well as MEF Hdh Q111/111 cells were smaller, showed higher proliferation rates and higher levels of phosphorylated mTOR pathway components compared to their wild type counterpart. Both ST Hdh cell lines displayed chromosome multiplications already at early passages, although the phenotype was more severe in ST Hdh Q7/7 cells. No marked chromosome abnormalities were found in the MEF cells. Results from fluorometric cell viability assays indicated that ST Hdh Q111/111 cells had reduced cell viability and increased cell mortality. This was not supported by the results from flow cytometry, the readouts of which are likely to be unaffected by cell size and proliferation. Conclusions: Differences in cell size and proliferation are characteristics of ST Hdh Q111/111 cells and might be caused by altered mTOR-related signalling. These phenotypes appear to be a general feature of HD, as they are also found in the second cell model. The different degree of genomic instability in wild type and mutant ST Hdh cells puts the usefulness of the wild type cells as controls in question. Furthermore, cell size and proliferation phenotypes are likely to confound test results and lead to inaccurate conclusions. Thus, our observations suggest that careful experimental design and well-considered data analysis are crucial when using this cell model.